Symposium 5: A Social Media Networked Learning Ecology Perspective - Bonzo, Justin (Proceedings of the International Conference on Networked Learning, 2012)
Learning Technology Professionals (LTPs) use social media as a networked learning environment (ecology) for their own professional learning. This is done through reading and contributing to blogs, wikis, Twitter, Facebook, social bookmarking, etc. The various elements of social media and the connections (people, information, resources) that link them together make up the networked learning ecology. Specifically, this research draws from the literature on learning ecologies (Barron, 2004, Brown, 2002, Frielick, 2004, Nardi and O'Day, 2000, Siemens, 2008b), networked learning (Banks et al., 2004, Goodyear et al., 2004, Jones et al., 2008, Steeples and Jones, 2002, Wasson et al., 2003), and on the growing amount of literature on social media in education. The individual concepts (social media, networked learning, learning ecology) of a SMNLE have been researched in the context of elementary and higher education, but there seems to be much less research in how these concepts individually apply to professional development and learning. Furthermore, the joint concept of a SMNLE has not been researched. In addition, there seems to be little if any research in the conception held by LTPs of the relationships, connections and links that exist in their SMNLE. By researching the conceptions of connections that LTPs hold, this research aims to add to the current body of research and provide insight into the experiences of those that are pushing the envelope about social media technologies involved in connecting with learning. The phenomenon I plan to research is that of the relationships within the networked learning ecology of LTPs. The phenomenon will be researched by looking at the variation in conception and perception of these connections by LTPs. In order to investigate the variation of meaning and ways of understanding the connections in their social media based learning ecologies, a phenomenographic approach for this research is being used. This allows for a description of the range of the perceiving and experiencing the phenomenon of learning ecology connections that LTPs experience. By using a phenomenographic approach, the research will be able to show how learning technology professionals conceive and perceive of the connections within a networked learning ecology.